A macro-level circular economy index: theoretical proposal and application in European Union countries - de Oliveira Frascareli, Fernanda Cortegoso [UNESP]; Furlan, Marcelo; Mariano, Enzo Barberio [UNESP]; Jugend, Daniel [UNESP] (Springer Nature, 2023)
The objective of this study was to propose a circular economy index applicable at a macro-level (i.e., countries). To achieve this objective, the snowball approach to literature reviews was adopted to find possible macro-level circular economy dimensions and indicators. Then, 10 indicators relating to these dimensions were identified in international databases. Finally, it was applied the benefit of the doubt (BoD) approach for data envelopment analysis (DEA), social network analysis (SNA) and principal component analysis (PCA) to build a macro-level circular economy index (MaCEI) for 18 European Union countries. The main results were as follows: (i) the identification of 52 potential indicators related to the circular economy at a macro-level were divided into 10 dimensions, (ii) a ranking of the performance of the 18 European countries in terms of their circular economy, (iii) the identification and analysis of the best circular economy practices at a national level (benchmarks), and (iv) the establishment of targets for each country. By offering a circular economy indicator and a well-established country ranking, this study contributes to the effective development of environmental standards that support public policies and national programs on the circular economy, in addition to guiding policy managers in driving the adoption of the circular economy at a macro-level.
Keywords: Benefit of the doubt; Circular economy; Data envelopment analysis; European Union; Macro-level; Social network analysis